Prevalence and 6‐month recovery of olfactory dysfunction: a multicentre study of 1363 COVID‐19 patients - Lechien, J. R.; Chiesa‐Estomba, C. M.; Beckers, E.; Mustin, V.; Ducarme, M.; Journe, F.; Marchant, A.; Jouffe, L.; Barillari, M. R.; Cammaroto, G.; Circiu, M. P.; Hans, S.; et al. (Journal of internal medicine, 2021)
Objective To investigate prevalence and recovery of olfactory dysfunction (OD) in COVID‐19 patients according to the disease severity. Methods From 22 March to 3 June 2020, 2581 COVID‐19 patients were identified from 18 European hospitals. Epidemiological and clinical data were extracted at baseline and within the 2‐month post‐infection. Results The prevalence of OD was significantly higher in mild form (85.9%) compared with moderate‐to‐critical forms (4.5–6.9%; P = 0.001). Of the 1916 patients with OD, 1363 completed the evaluations (71.1%). A total of 328 patients (24.1%) did not subjectively recover olfaction 60 days after the onset of the dysfunction. The mean duration of self‐reported OD was 21.6 ± 17.9 days. Objective olfactory evaluations identified hyposmia/anosmia in 54.7% and 36.6% of mild and moderate‐to‐critical forms, respectively (P = 0.001). At 60 days and 6 months, 15.3% and 4.7% of anosmic/hyposmic patients did not objectively recover olfaction, respectively. The higher baseline severity of objective olfactory evaluations was strongly predictive of persistent OD (P < 0.001). Conclusion OD is more prevalent in mild COVID‐19 forms than in moderate‐to‐critical forms. OD disappeared in 95% of patients regarding objective olfactory evaluations at 6 months.